Cover Picture: π–π Interactions: Influence on Molecular Packing and Solid‐State Emission of ESIPT and non‐ESIPT Motifs (Asian J. Org. Chem. 7/2016). Issue 7 (27th June 2016) - Padalkar, Vikas S.; Sakamaki, Daisuke; Kuwada, Kenji; Horio, Akifumi; Okamoto, Haruka; Tohnai, Norimitsu; Akutagawa, Tomoyuki; Sakai, Ken‐ichi; Seki, Shu
Abstract : Non‐covalent interactions in benzothiazole motifs with donor–acceptor (D—A) blocks modulate dramatically the efficiency and the color of emission through excited‐state intramolecular electron transfer (ESIPT) and intramolecular charge transfer (ICT) processes. Correlation between structures and optical properties revealed the π–π interactions modulated by the electronic communication within the D–A blocks as responsible for the interplay of ESIPT and ICT, providing a unique approach to design highly emissive solid‐state π‐conjugated chromophores based not only on ESIPT but also on aggregation‐induced emission. More information can be found in the full paper by S. Seki and co‐workers onpage 938 in Issue 7, 2016 (DOI:10.1002/ajoc.201600159 ).